2007
DOI: 10.1029/2007wr005915
|View full text |Cite
|
Sign up to set email alerts
|

Controls on major solutes within the drainage network of a rapidly weathering tropical watershed

Abstract: [1] Surface water chemistry in the main stem and source points of the Rio Icacos basin (Luquillo Experimental Forest, Puerto Rico) was studied to investigate the factors regulating spatial variability in major solutes in a rapidly weathering landscape. We sampled along the main stem as well as at small source points at high elevation where fresh bedrock is frequently exposed, and at low elevation in the floodplain/colluvial plain of the main stem. Concentrations of silicon, alkalinity, and the sum of base cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 43 publications
1
23
1
Order By: Relevance
“…We found sulfate concentration many times higher than in most of the largest river systems of the world and in the fastest weathering regimes of a silicate terrane on the earth surface (McDowell and Asbury 1994;Meybeck and Ragu 1997;Gaillardet et al 1999;Bhatt and McDowell 2007;Tartai et al 1998;Bhatt et al 2014a). Takeuchi et al (2012) found that various organisms such as insects, copepods, and algae live in ponds in the debris-covered area of this glacier.…”
Section: Overview and Composition Of Major Ionsmentioning
confidence: 56%
See 4 more Smart Citations
“…We found sulfate concentration many times higher than in most of the largest river systems of the world and in the fastest weathering regimes of a silicate terrane on the earth surface (McDowell and Asbury 1994;Meybeck and Ragu 1997;Gaillardet et al 1999;Bhatt and McDowell 2007;Tartai et al 1998;Bhatt et al 2014a). Takeuchi et al (2012) found that various organisms such as insects, copepods, and algae live in ponds in the debris-covered area of this glacier.…”
Section: Overview and Composition Of Major Ionsmentioning
confidence: 56%
“…*K) among the ponds within Lirung debris areas appeared lower than the calculated ratios from Langtang-Narayani river system in central Nepal Himalayas (unpublished data) and much lower than the calculated ratios from different positions of the Rio Icacos (which drains a tropical rain forest) that has the fastest documented weathering rates of any silicate terrain in the world (McDowell and Asbury 1994;White and Blum 1995;Bhatt and McDowell 2007). The wide variation in Si/ (*Na ?…”
Section: Hypothesis 3: Weathering Extent and Controlling Parametersmentioning
confidence: 72%
See 3 more Smart Citations